Brain Drain from Turkey: The Case of Professionals Abroad - Nil Demet Güngör; Aysit Tansel (Turkish Economic Association, 2007)
The paper presents research findings on the return intentions of Turkish professionals residing abroad. The study uses a descriptive framework to establish the validity of several proposed models of non-return. The results are based on an internet survey of Turkish professionals abroad. Correspondence analysis is used to examine the relationship between return intentions and various factors that may affect this intention. The results emphasize the importance of student non-return versus traditional brain and appear to complement the various theories of student non-return. The respondents appear to come from relatively well-to-do families with highly educated parents. Many have earned their degrees from universities that have foreign language instruction. The recent economic crises in Turkey have negatively affected return intentions. We verify that return intentions are indeed linked closely with initial return plans, and that this relationship weakens with stay duration. Specialized study and work experience in the host country also all appear to contribute to explaining the incidence of non-return. Return intentions are weaker for those working in an academic environment. These results lead to important policy implications, some of which include the training of individuals for academic positions at domestic institutions, supporting study abroad for shorter periods and improving academic facilities in Turkeys newly established universities. The government may support public and private R&D centers to increase the employability of returnees, but also to improve the quality of the higher education system in order to both reduce the need for education abroad and to increase the attractiveness of universities as prospective employment places for those acquiring education and experience abroad.
Keywords: F22; J61; O15; 330; skilled migration; brain drain; return migration; return intentions; higher education; Turkey; Brain Drain; Hochqualifizierte Arbeitskräfte; Rückwanderung; Türkei